A computational approach to investigate the suitable ETL for lead-free CsGeI3 based perovskite solar cell. (2021) - Raj, Abhishek; Kumar, Manish; Singh, Pramod K.; Chandra Singh, Ram; Bherwani, Hemant; Gupta, Ankit; Anshul, Avneesh
Abstract: Over the past 10 years, organic–inorganic lead halides perovskite solar cell achieved rapid evaluation in the field of photovoltaic technology. The developed devices already achieved maximum power conversion efficiency of 25.2%. Despite of this significant advancement the toxicity of lead and stability of device is the major concern. In the present study, computational approach is used to simulate perovskite solar cell with lead-free perovskite light absorbing layer. Inorganic lead-free light harvesting layer CsGeI3 is simulated with different electron transporting layers (ETLs) to investigate an appropriate ETL. The PSCs with C60 and SnO2 ETLs exhibited superior device performance with open-circuit voltage (VOC ) of 0.64 V, 0.63 V; current density (JSC ) of 20.64 mA/cm 2, 21.60 mA/cm 2 ; fill factor (FF) of 63.30%, 61.99%; and power conversion efficiency (PCE) of 8.45%, 8.46% respectively.